PULP SULFAT DARI BATANG KELAPA (Sulphate pulp from coconut trunk) - Rena M Siagian; M Rosid (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
This paper deals with the study of the influence of active alkali concentration to the properties of coconut trunk (cocos nucifera L.) sulphate pulping trials were conducted in laboratory digester with the cooking liquor circulation, using three levels of active alkali, i,e 14, 16 and 18% cooking sulfidity was 25%, wood to liquor ratio was 1:4, and maximum temperature was 165°c maintained for 120 minutes.Pulp yields from coconut trunks are ranged from 39.9 to 40.9% with permanganate number of 8.17 to 11.15. the increasing amount of active alkali has no significant influence to the yield, and overall physical properties of the pulp but tear factor. The higher active alkali concentration, the lower permanganate number and the higher alkali consumption. It is hope that the sulphate pulping of coconut trunk with active alkali of 16% would give adequate yield and processing properties.